EVALUASI KEPATUHAN PERPAJAKAN DAN UPAYA TAX PLANNING UNTUK MEMINIMALISASI PAJAK PENGHASILAN PADA PERUSAHAAN JASA ANGKUTAN PT XYZ - BINTORO PUTRO, ALBERT (Berkala Ilmiah Mahasiswa Akuntansi)
The study was done in order to evaluate compliance with the implementation of the obligations of Article 21 Income tax and VAT on PT XYZ, as well as tax planning efforts (tax planning) in the framework of the acquisition of fixed assets, personnel costs, and tax planning in addition to acquisition of fixed assets and the cost of employees at PT XYZ. The results showed that PT XYZ has been adhering to the rules of taxation in the absence of a warning letter or a fine or penalty tax administration. On the acquisition of property and equipment leasing appears to be profitable, because it allowed a greater burden and make the income tax becomes smaller. PT XYZ should replace the provision in kind with food so that money can be expensed to minimize income taxes. Another thing you can do as a form of tax planning is a nominative list for expenditure in the interests of entertainment.